Shared wollen patterns / Härkönen, Mäkinen, Huhmarniemi & Rinne - Härkönen, Elina; Huhmarniemi, Maria; Rinne, Jari (Lapin yliopisto, 2019)
The installation examines a shared cultural heritage of the Arctic through traditional knitting patterns. The pieces were collected in collaboration with knitters around the Arctic who have shared their knowledge of their regional knitting traditions. The knitted pieces represent pieces of cultural identity and heritage. Attached together the pieces show similarities and differences between different traditions. The soundscape dislodges actual knitting sounds and creation of stories defecting beyond palpable physical patterns. The installation aims to make the handcraft traditions visible and demonstrate their dimension as a shared tradition of knitting that brings people together. Alluring audio cues open hearing for “knitting state of mind” like slowing down, cosy feelings and safe space for sharing stories